Collaborative and individual approach in the flipped learning by assessing students on the basis of spatial data quality control - Bec, Damijan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2015)
A variant of flipped learning based on intensive usage of geomedia in geography and geoinformatics has been developed and presented in the article. Students assessed quality of mapping according to ISO standard. The results show that individuals are considerably better than groups, especially in tasks which required the use of critical judgement, deeper understanding and creative thinking. However, groups are more successful in finding unique differences, where synergy effect of the collaborative learning is an important factor.
Keywords: didactic method; didaktika; geografija; geography; learning; skupinsko delo; učenje; visokošolski študij